Vimentin-positive circulating tumor cells as a biomarker for diagnosis and treatment monitoring in patients with pancreatic cancer - Wei, Tao; Zhang, Xiaoyu; Zhang, Qi; Yang, Jiaqi; Chen, Qi; Wang, Jianxin; Li, Xiang; Chen, Junye; Ma, Tao; Li, Guogang; Gao, Shunliang; Lou, Jianying; et al. (Cancer letters, 2019)
The identification of circulating tumor cells (CTCs) relies on epithelial tumor cell markers. In the present study, we aimed to determine whether cell-surface vimentin could be a biomarker to isolate CTCs in pancreatic ductal adenocarcinoma (PDAC). Vimentin was identified as highly expressed on the surface of mesenchymal-phenotype pancreatic tumor cells. Vimentin+ CTCs were detected in 76% of patients with PDAC (76/100) using CTCs enriched via a microfluidic assay. A cut-off value of two vimentin+ CTCs distinguished patients with PDAC from healthy individuals. Combined vimentin+ CTCs and Carbohydrate antigen 19–9 provided favorable diagnostic potency, with an area under the curve of 0.968. Vimentin+ CTCs counts correlated with the change in tumor burden for patients undergoing resection. Significantly reduced CTC counts were observed after chemotherapy in subjects that responded to treatment. Preoperatively higher CTCs counts correlated with shortened recurrence-free survival. Taken together, vimentin+ CTCs could be a reliable biomarker in pancreatic cancer. The enrichment of mesenchymal CTCs complements the strategy of capturing epithelial CTCs, allowing a more thorough interrogation of the biology and clinical significance of CTCs in PDAC. •Vimentin is expressed on the surface of pancreatic tumor cells with mesenchymal phenotype.•Vimentin+ CTCs distinguish PDAC patients and healthy individuals, and confer favorable diagnosis performance when combined with CA19-9.•Vimentin+ CTCs correlate with tumor burden and prognosis.